Pengaruh Profitabilitas, Leverage, dan Umur Perusahaan Terhadap Praktik Tax Avoidance: Studi Kasus Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2023 - Imam Prayoga; Gita Desyana; Syarbini Ikhsan (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to investigate the influence of profitability, leverage, and company age on tax avoidance practices in energy sector companies in Indonesia that are listed on the Indonesia Stock Exchange. The data were analyzed using multiple regression methods on a sample of 46 financial reports from the years 2020 to 2023. The results of the analysis show that profitability does not have a significant effect on tax avoidance, while leverage also does not have a significant effect. However, company age has been proven to have a significant effect on tax avoidance. Nonetheless, these three variables have a simultaneous effect on tax avoidance. This research is relevant for improving tax policies and reducing tax avoidance practices that are detrimental to the state.